Associations of Alcohol and Drug Misuse with Hospital Outcomes in Traumatic Injury Patients. (17th February 2020) - Grady, Edmund; Hayward, R. David; Edhayan, Elango
Abstract: Background : Traumatic injury is one of the most common causes of mortality worldwide. Previous research suggests that alcohol and drug misuse can increase the risk of experiencing these injuries. Method : Data on all hospital admissions due to traumatic injury in the Detroit metropolitan area between 2006 and 2014 were obtained from the Michigan State Inpatient Database. Patients with no recorded substance misuse comorbidity were compared with those who had (a) alcohol misuse comorbidity only, (b) drug misuse comorbidity only, and (c) both alcohol and drug misuse comorbidities. Outcomes examined included in-hospital mortality, length of stay, and total cost of care. Results : Generalized linear modeling was used to examine the relationship between substance misuse comorbidities and each of the three outcomes. Lower mortality was related to drug and drug/alcohol misuse. Longer length of stay was related to alcohol, drug, and alcohol/drug misuse. Total costs were higher for patients with comorbid alcohol misuse, but lower for those with comorbid drug misuse. These patterns of results were not changed after controlling for differences in background demographics and injury characteristics. Discussion : Alcohol and drug misuse were highly prevalent in trauma patients, in comparison to estimate for the US population as a whole. The relationship between substance misuse comorbidity and outcomes among trauma patient is not straightforward. Substance misuse of all types was related to longer hospitalization, but its association with cost and mortality was mixed. Assessment of substance misuse background at intake may help optimize care for trauma patients.